Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.7759/cureus.27379
|View full text |Cite
|
Sign up to set email alerts
|

Acute Adverse Effects of Vaccines Against SARS-COV-2

Abstract: The global struggle against the impact of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) on physical and mental health and on economic and social aspects of human life continues even after two and a half years have passed since the emergence of this virus. The development of vaccines was a milestone. By June 2022, billions of people have been vaccinated against the deadly virus. However, like any other vaccine, the various vaccines against coronavirus disease 2019 (COVID-19) also cause a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
2
2
0
Order By: Relevance
“…Also, these findings were consistent with the results of Oxford AstraZeneca's clinical trial [25]. A strong immune reaction in young people under 50 due to robust inflammatory cytokines production may explain this high frequency of side effects in younger recipients [40]. Furthermore, we found that females presented significantly more adverse events following the first dose and second dose vaccination than males.…”
Section: Plos Onesupporting
confidence: 91%
“…Also, these findings were consistent with the results of Oxford AstraZeneca's clinical trial [25]. A strong immune reaction in young people under 50 due to robust inflammatory cytokines production may explain this high frequency of side effects in younger recipients [40]. Furthermore, we found that females presented significantly more adverse events following the first dose and second dose vaccination than males.…”
Section: Plos Onesupporting
confidence: 91%
“…The majority of the participants of the study reported no or mild difficulties due to the post vaccination side effects, which resolved within one to two days for 45% of the participants (n=523). Other studies conducted in Pakistan analyzing the impacts of primary vaccination corroborate our study results 13,14 . However, another study has also reported some serious adverse reactions in Pakistani population like limb paralysis, heart attack, diplopia, renal failure and death 15 .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies conducted in Pakistan reported mild adverse reactions of the vaccines and the factors associated with these side effects [13][14][15] .…”
Section: Discussionmentioning
confidence: 94%
“…Separate models were run for each predictor variable and all models were adjusted for age, sex, body mass index, vaccine type, and education. These variables were included based on findings from other studies 14 , 49 52 . Results are presented as odds ratios (OR) with their 95% confidence intervals (CI) and two-sided p -value.…”
Section: Methodsmentioning
confidence: 99%